2003
DOI: 10.1046/j.1600-0412.2003.00223.x
|View full text |Cite
|
Sign up to set email alerts
|

C‐reactive protein in vaginal fluid of patients with preterm premature rupture of membranes

Abstract: Increased vaginal fluid CRP concentration is associated with intraamniotic infection and funisitis. As CRP is produced by hepatocytes and does not cross the placenta, its measurement in vaginal fluid might be an additional parameter for the assessment of fetal well-being in patients with premature PROM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 27 publications
2
15
0
2
Order By: Relevance
“…These results indicate that CRP does not cross the placenta. 46 In previous studies, elevated CRP levels found in amniotic fluid were associated with higher adverse pregnancy outcome reflected in preterm deliveries, intra-amniotic infection, chorioamnionitis, funisitis, and preeclampsia. 22,[47][48][49] In our study, we found that women with elevated CRP levels in plasma had a 3-fold increased risk for low birth weight compared with those who did not show signs of systemic inflammation; however, when adjusted for P. falciparum infection, no independent effect was observed.…”
Section: Discussionmentioning
confidence: 88%
“…These results indicate that CRP does not cross the placenta. 46 In previous studies, elevated CRP levels found in amniotic fluid were associated with higher adverse pregnancy outcome reflected in preterm deliveries, intra-amniotic infection, chorioamnionitis, funisitis, and preeclampsia. 22,[47][48][49] In our study, we found that women with elevated CRP levels in plasma had a 3-fold increased risk for low birth weight compared with those who did not show signs of systemic inflammation; however, when adjusted for P. falciparum infection, no independent effect was observed.…”
Section: Discussionmentioning
confidence: 88%
“…Di Naro et al 6 . found that increased vaginal fluid C‐reactive protein concentration is associated with intra‐amniotic infection and funisitis and that there is a significant correlation between its amniotic fluid and vaginal fluid concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Although the assessment of various inflammatory mediators in the amniotic fluid is highly accurate in the diagnosis of amnionitis, it requires the performance of invasive amniocentesis. Moreover amniocentesis may be difficult to perform in patients with pPROM because the amniotic fluid volume is often reduced 6 . Therefore, non‐invasive methods of detecting intrauterine infection are desirable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some inflammatory mediators may also be detected in vaginal or cervical secretions, and it is probable that their concentrations in the vaginal compartment, especially after rupture of membranes, reflect their intraamniotic concentrations. 10,11 C-reactive protein (CRP) is an acute phase reactant produced by liver cells in response to interleukin-6 synthesized during infection, and it was proved that increased CRP values strongly indicate infectious complications. 12 Although maternal serum level of CRP slightly increases within gestational age, still this marker is used as an indicator of intrauterine infection, especially in pPROM cases [13][14][15][16][17][18] nevertheless reports that its benefits are conflicting.…”
Section: Introductionmentioning
confidence: 99%